2014
DOI: 10.1681/asn.2013101043
|View full text |Cite
|
Sign up to set email alerts
|

With Complements from ANCA Mice

Abstract: ANCA is found in the vast majority of patients with active smallvessel vasculitis. This disease group includes what is now known as granulomatosis with polyangiitis, microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis, and a renallimited disease form featuring necrotizing crescentic pauciimmune GN (NCGN). 1 ANCA is directed against neutrophils and monocytes and was initially considered a helpful clinical diagnostic and disease activity-monitoring tool. 2 Over the last 3 decades, numerous AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Until recently, it was commonly accepted that serum C3 (sC3) and C4 (sC4) levels are normal in patients with AAV, which probably led to underestimate the pathogenic importance of the complement system in AAV (2). However, previous studies showed that most patients have at least focal complement tissue deposition (3), but the relevance of this observation was underpinned by the important ANCA discovery and the subsequent "pauci-immune/pauci-complement paradigm."…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, it was commonly accepted that serum C3 (sC3) and C4 (sC4) levels are normal in patients with AAV, which probably led to underestimate the pathogenic importance of the complement system in AAV (2). However, previous studies showed that most patients have at least focal complement tissue deposition (3), but the relevance of this observation was underpinned by the important ANCA discovery and the subsequent "pauci-immune/pauci-complement paradigm."…”
Section: Introductionmentioning
confidence: 99%
“…11 C5a and C5a receptor (C5aR, or CD88) play a central role in the pathogenesis of AAV. [12][13][14] C5a can prime and activate neutrophils, 15 which release C5a when stimulated by inflammatory cytokines such as TNFa. 16 C5a, acting on C5aR, is a potent neutrophil chemoattractant and agonist 17 and can decrease neutrophil deformability, slowing their ability to traverse small blood vessels, particularly in the presence of ANCA.…”
mentioning
confidence: 99%
“…This was considered to result from negligible complement activation. Moreover, hypocomplementaemia is uncommon in AAV patients [2].…”
mentioning
confidence: 99%